PENDAMPINGAN MANAJEMEN USAHA UNTUK PENGEMBANGAN UMKM SELEUD DI SAWO JAJAR KOTA MALANG - Elisa; Errica Dwitanti; Agung Winarno; Agus Hermawan (Jurnal Pemantik, 2022)
UMKM are one of the important economic sectors in Indonesia. The fact is that UMKM have played an important role in the Indonesian economy to date. When Covid 19 became a global problem, it happened in 2019. This virus spread to various countries, one of which is Indonesia. One of the economic impacts felt by UMKM players is a decrease in sales turnover. Development of Managerial Insights is a course whose program teaches students to do community service. Which activity is a form of training in the form of Community Service. This community service aims to help UMKM to increase sales. With this problem, we are the students at the Malang State University Master of Management who carry out this service activity which will be carried out from the beginning of September 2022 to the end of November 2022 at UMKM Seleud, which is addressed at Jl. Sunda Strait II D3/24 Sawojajar Malang city. The methods used in socialization and education activities include identifying work programs, training, and mentoring. The results of this series of community service activities are the development of attractive product logos, making business logos, more modern marketing, payments via QRIS and getting distributors hydroponic raw materials.